The Effect of Drive Training Method and Leg Length on Rally Ability in Rukun Tennis Club Players (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The background of this study is that there are still shortcomings, weaknesses, and lack of consistency of the Rukun Tennis Club players, especially in rallying, the average player hitting 0-4 strokes when expanding the rally. This study aims to analyze the drive and leg length training methods of the Rukun Tenis Club players in Kudus and is a quasi-experimental study with a sample of 16 people. The data analysis technique used is the technique of analysis of variance (ANAVA) 2x2 factorial design at a = 0.05. The results of the type of exercise variable were obtained fcount > ftable = 6.61 > 4.49, the results of the variable leg length were obtained fcount < ftable = 2.60 < 4.49, the results of the variable type of leg length exercise obtained fcount< ftable = 2.57< 4.49. The conclusion of this study is that there are differences in the effect of drive ten on the baseline exercise and drive kamikaze exercise on the ability to rally 3 minutes in Rukun Tenis Club players in 2021. There is no difference in the effect of long and short legs on the ability to rally 3 minutes in Rukun Tenis Club players In 2021, there is no interaction between the drive training method and the length of the legs on the 3-minute rally ability in the Rukun Tennis Club players in 2021.